10 recommendations for strengthening citizen science for improved societal and ecological outcomes: A co-produced analysis of challenges and opportunities in the 21st century - Jack S Nunn; Håkon da Silva Hyldmo; Lauren McKnight; Heather McCulloch; Jennifer Lavers; Julie Old; Laura Smith; Nicola Grobler; Cheryl Tan Kay Yin; Wing Yan Chan; Candice Raeburn; Nittya S. M. Simard; et al. (PLoS ONE, 2026)
Citizen science plays an increasingly important role in generating scientific knowledge and supporting environmental and social action. However, its potential to address complex global challenges remains underutilised. This study explores how citizen science can be improved by involving the public in all stages of scientific research. Using participatory research methods, online surveys and group discussions were conducted with researchers, citizen scientists, and Indigenous participants. Thematic coding was used to identify key challenges, opportunities, and best practices to enhance citizen science initiatives. Additionally, nine case studies were reported using the Standardised Data on Initiatives (STARDIT) reporting tool. The study identified key strategies for improving involvement, engagement and retention in citizen science initiatives. Findings underscore the importance of inclusive, evidence-informed approaches such as targeted outreach, fair compensation, tailored support, and co-creation practices. Ensuring data quality and fostering trust require adherence to FAIR data principles (findable, accessible, interoperable and reusable), transparent validation and sharing processes, and establishing ethical research partnerships. Persistent challenges include short-term funding, which undermines long-term project sustainability, and the lack of centralised support for ethics and project management. Formal recognition of citizen scientists through co-authorship, standardised training, and professional development opportunities can further strengthen involvement and build capacity. Finally, emerging technologies, including artificial intelligence and open data platforms, present opportunities to scale and improve efficiency, provided they are implemented with appropriate ethical safeguards and investment. Drawing together these insights, we provide 10 actionable recommendations for citizen science in the 21 st century. These highlight the importance of embedding citizen science in national research infrastructure, education, and policy, alongside consistent evaluation and reporting, to improve its inclusivity, longevity, and impact. We conclude by arguing that as the world confronts climate change, public health crises, and biodiversity loss, broader public involvement in science is key for equitable, efficient and evidence-informed responses.